1992
DOI: 10.2190/2am4-7gtq-nj46-9j1x
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Life Events and Coping in the Oldest-Old

Abstract: This paper compares older adults in their sixties, eighties, and 100s on personality, experience of life events, and coping. A secondary goal was to test a structural model of adaptation. Participants (165) filled out a personality inventory, life-event lists, and coping and mental health measures. Results revealed differences in personality: centenarians scored higher on dominance, suspiciousness, and imagination. While centenarians scored lower on active behavioral coping than other age groups, they used cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…For example, the 'old-old' may suffer from a higher prevalence of disability (Bruce, 2002;Chou and Chi, 2005), in addition to a declining sense of control over their own life (Mirowsky and Ross, 1992). But the 'old-old' may also have more effective coping mechanisms due to greater life experience, maturity and self-esteem (Gove et al, 1989;Martin et al, 1992;Mirowsky and Ross, 1992;Chou and Chi, 2005). Investigation of these age-based subgroups within late life may help clarify correlates of depression and the pathways leading to depression in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 'old-old' may suffer from a higher prevalence of disability (Bruce, 2002;Chou and Chi, 2005), in addition to a declining sense of control over their own life (Mirowsky and Ross, 1992). But the 'old-old' may also have more effective coping mechanisms due to greater life experience, maturity and self-esteem (Gove et al, 1989;Martin et al, 1992;Mirowsky and Ross, 1992;Chou and Chi, 2005). Investigation of these age-based subgroups within late life may help clarify correlates of depression and the pathways leading to depression in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that, in comparison with the other age groups, the oldest-old are more vulnerable to depression because they are more likely to expose the risk factors contributing to depression such as frailty, physical illnesses, bereavement, and loneliness (Bruce, 2002;Blazer, 2002). On the other hand, they might have more effective coping strategy than the other elderly people due to life experience so that they might counter those adverse situations which might lead to depression (Martin et al, 1992;Mirowsky and Ross, 1992). Moreover, depression might diminish in the oldest-old as a consequence of selective survival (Blazer and Koenig, 1996;Haynie et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to personality, previous centenarian studies have reported that centenarians have distinguishing personality profiles in comparison with younger controls (Inagaki et al 1996;Martin et al 2002;Martin et al 1992;Samuelsson et al 1997;Shimonaka et al 1996). These characteristics may help to reveal key personality traits for longevity.…”
mentioning
confidence: 97%